A novel photoanode with high flexibility for fiber-shaped dye sensitized solar cells. Issue 16 (8th April 2016) - Liu, Guicheng; Gao, Xue; Wang, Hui; Kim, A-Young; Zhao, Zhenxuan; Lee, Joong Kee; Zou, Dechun
Abstract : A completely flexible photoanode with a TiO2 micron-cone-nanowire array could bend to a curvature radius of 0.45 mm, which is the most flexible Ti-based photoanode to date. Abstract : A completely flexible fiber-shaped dye sensitized solar cell has been truly realized for the first time, due to a novel photoanode with a TiO2 micron-cone-nanowire array structure prepared by a simple two-step process. The TiO2 micron-cone array, made using an electrochemical method, is used as a frame for a novel photoanode, with its roots sinking deep down into a Ti wire substrate. The TiO2 nanowire array is coated onto the TiO2 micron-cone surface by a hydrothermal reaction to form a dye-adsorption layer to the enhance power conversion efficiency of the novel device. With a high dye-adsorption capacity and strong combination between the TiO2 micron-cone and Ti substrate, the minimum bending radius of the photoanode could reach 0.45 mm, and 96.6% retention of the initial conversion efficiency was obtained after bending 100 times.